2002
DOI: 10.1016/s0886-3350(02)01491-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pupil dilation on the accuracy of the IOLMaster

Abstract: Dilating the pupil did not adversely affect the clinical accuracy of the IOLMaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…Thus, no significant change in AL is produced in response to pupil dilation using both the IOLMaster 500 © and LENSTAR © [6][7][8][9][10]. The slight, though significant, increase in CCT observed in our study is consistent with the findings of other authors, who noted significant increases in CCT after pupil dilation with tropicamide eye drops [14,15].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, no significant change in AL is produced in response to pupil dilation using both the IOLMaster 500 © and LENSTAR © [6][7][8][9][10]. The slight, though significant, increase in CCT observed in our study is consistent with the findings of other authors, who noted significant increases in CCT after pupil dilation with tropicamide eye drops [14,15].…”
Section: Discussionsupporting
confidence: 90%
“…In three studies examining the effect of pupil dilation in IOLMaster 500 © measurements [6][7][8], no effects were observed on AL and only one study reported a significant difference in pre-and post dilation MK data [6]. In addition, in the only one study in which the ACD was measured, this variable was found to increase after pupil dilation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some studies on dilatation and IOL measurement have found that pupil dilatation does not affect the accuracy of the IOLmaster [4]. Nevertheless, some surgeons believe that dilatation of the pupil causes patients to have poor fixation [4].…”
mentioning
confidence: 99%